Stabilization of thermally unstable photoisomers of pyridinium-functionalized hemithioindigo switches by host-guest complexation. (3rd December 2021) - Bruekers, Jeroen P.J.; Bakker, Rob; White, Paul B.; Tinnemans, Paul; Elemans, Johannes A.A.W.; Nolte, Roeland J.M.
Abstract: Pyridine-functionalized hemithioindigo photoswitches ( Z )-6-( Z )-8 were obtained by an aldol condensation of benzothiophenone 5 with the appropriate pyridinecarbaldehyde. These compounds were methylated with methyl iodide or methyl triflate to obtain pyridinium-functionalized hemithioindigo photoswitches ( Z )-2 -( Z )-4 . The resulting compounds ( Z )-2 -( Z )-4 and ( Z )-6 -( Z )-8 could be isomerized to the ( E )-isomer with light of λ = 470 nm, with relative abundances of the photoisomers up to 96%. All photoswitches except ( Z )-2 could be isomerized back to the ( Z )-state with light of longer wavelengths. For ( Z )-2 this process of adopting a new photostationary state was slower compared to the thermal relaxation. Switches ( Z )-2 -( Z )-4 were capable of binding in a porphyrin cage host (H 2 1 ) with association constants that increased with the distance between the positive charge and the central double bond of the switch: (( Z )-2 < ( Z )-3 < ( Z )-4 ). As a result of the complexation with H 2 1 the thermal relaxation rate of ( E ) → ( Z ) isomerization decreased up to 3-fold. Graphical abstract: Image 1